MK-5172: a second-generation protease inhibitor for the treatment of hepatitis C virus infection. (May 2014) - Gentile, Ivan; Buonomo, Antonio Riccardo; Borgia, Federico; Zappulo, Emanuela; Castaldo, Giuseppe; Borgia, Guglielmo
<x xml:space="preserve">Abstract</x> Introduction: Approximately 170 million people worldwide are chronic carriers of the hepatitis C virus (HCV). Twenty-five percent of them develop liver cirrhosis and hepatocellular carcinoma during their life. Successful antiviral treatment dramatically reduces the risk of disease progression. HCV infection is treated with pegylated interferon and ribavirin; the addition of a protease inhibitor (boceprevir or telaprevir) can also be considered for patients with genotype 1. Areas covered: This review summarizes the data about the pharmacokinetics, pharmacodynamics, efficacy and safety of <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=MK-5172&logicalOpe1=OR&field2=articletitle&text2=MK-5172&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">MK-5172, a second-generation inhibitor of HCV NS3/4A protease. Expert opinion: The pharmacokinetic profile allows for once-a-day administration. Combined with pegylated interferon and ribavirin, MK-5172 results in a high rate of HCV eradication (in about 90% of cases) and a better outcome than boceprevir-based triple therapy. Also in interferon-free combinations, MK-5172-associated eradication rates are very high (89 – 100%). MK-5172 has a higher barrier to resistance than first-generation protease inhibitors and is active against most variants associated with resistance to first-generation protease inhibitors. Tolerability and safety profile are good. Although data are limited, MK-5172 appears to overcome most of the drawbacks of the first-generation protease inhibitors and is thus a very promising agent to be used in combination with other antivirals to eradicate HCV infection.